In Search of Matthew Effects in Reading. (September 2016) - Protopapas, Athanassios; Parrila, Rauno; Simos, Panagiotis G.
The concept of Matthew effects in reading development refers to a longitudinally widening gap between high achievers and low achievers. Various statistical approaches have been proposed to examine this idea. However, little attention has been paid to psychometric issues of scaling. Specifically, interval-level data are required to compare performance differences across performance ranges, but only ordinal-level data are available with current literacy measures. To demonstrate the interpretability problems of contrasting growth slopes, we use data from a longitudinal study of literacy development. We explore the possibility of comparing across ages, matched for performance, and we examine the consequences of nonlinear growth, temporal lag estimates, and individual differences in developmental progression. We conclude that, although conceptually appealing, the widening gap prediction is not empirically testable.